THE IMPORTANCE OF IMAM TIRMIDHI’S ‘SUNAN’ IN ISLAMIC HISTORY (American Journal of Research in Humanities and Social Sciences, 2024)
This article presents reflections on the life and hadith activities of Imam Termizi. It also makes scientific conclusions about the significance of Imam Termizi’s work ‘Sunan Termizi’ in the history of Islam and its role today.